2018
DOI: 10.1007/s11469-018-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adults and Facebook Use: the Validation of the Bergen Facebook Addiction Scale (BFAS)

Abstract: Based on the six key components of addiction, the Bergen Facebook Addiction Scale (BFAS) is a widely used instrument to assess Facebook addiction. This study aimed to conduct a psychometric validation in a Portuguese sample of emerging adults (ages 18 to 29 years). The construct validity analyses confirmed the one-factor solution and a statistically significant association found between Facebook addiction and Preference for Online Social Interaction, measured by the Generalized Problematic Internet Use Scale 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…The BFAS psychometric properties have been assessed in different international studies, including Poland [ 26 ], Portugal [ 27 , 28 , 29 ], Brazil [ 30 ], Egypt [ 31 ], Tunisia [ 32 ], Peru [ 33 ], Pakistan [ 34 , 35 ], Bangladesh [ 36 ], Thailand [ 37 ], Turkey [ 38 ], Iran [ 39 ], and Italy [ 40 ]. Results demonstrated that satisfactory psychometric properties were found, including reliability and convergent validity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BFAS psychometric properties have been assessed in different international studies, including Poland [ 26 ], Portugal [ 27 , 28 , 29 ], Brazil [ 30 ], Egypt [ 31 ], Tunisia [ 32 ], Peru [ 33 ], Pakistan [ 34 , 35 ], Bangladesh [ 36 ], Thailand [ 37 ], Turkey [ 38 ], Iran [ 39 ], and Italy [ 40 ]. Results demonstrated that satisfactory psychometric properties were found, including reliability and convergent validity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding convergent validity, the BFAS scores were found to be positively associated with Problematic Internet Use and Internet Addiction [ 27 , 28 , 29 , 30 ], fear of missing out [ 33 ], social anxiety, loneliness, and depression [ 26 , 29 , 32 ]. Extraversion, narcissism, and low self-efficacy were also found to be associated with BFAS scores [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scales to assess PSMU in adolescence or young adults are often based on the general criteria of addictive disorders (cf. Six Core Components of Addiction Model by Griffith) [ 16 , 17 , 18 , 19 ] or on the related construct of Internet Gaming Disorder (IGD) [ 12 ]. The latter has been included as a condition warranting more research in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as the first and to date only member of Internet-related disorders [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prominent negative effects of social media use relates to problematic use stemming from dysregulated usage (Kuss and Griffiths, 2017 ; Radovic et al, 2017 ), often triggered by the design of the social media platforms and the prevailing data business model (Montag et al, 2019 ). However, the literature remains inconclusive, fragmented, and heavily skewed toward the investigation of a single, specific social media platform (e.g., Facebook) (e.g., see Pontes et al, 2016 ; da Veiga et al, 2019 ; Rozgonjuk et al, 2020a , b ; Sindermann et al, 2020 ; for exceptions Marengo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%